Room-temperature spin-glass behaviors and memory effects in Al-substituted Y3Fe5O12 epitaxial film grown by pulsed laser deposition - Takahiro Yoshino; Siyi Tang; Md Shamim Sarker; EMK Ikball Ahamed; Zhiqiang Liao; Hiroyasu Yamahara; Hitoshi Tabata; Munetoshi Seki (AIP Advances, 2025)
This study explores the magnetic properties of a thin film of Al-substituted Y3Fe5O12 grown on Y3Al5O12 (111) substrates using pulsed laser deposition. Spin-glass behavior was observed near room temperature in the film, with a spin-freezing temperature of 345 K achieved. This temperature is significantly higher than those previously reported for spin-glass systems based on Fe oxides. The film exhibited characteristic memory and rejuvenation effects below the spin-freezing temperature, which are explained by magnetic relaxation via metastable states within a multi-valley energy landscape featuring shallow activation energies. Additionally, photomagnetic memory effects were demonstrated using the magneto-optic effect of the film at room temperature. Our results highlight the potential application of the Al-substituted Y3Fe5O12 film in neuromorphic devices with low energy consumption.